The Trend of Audit Quality Development: A Scopus-Based Bibliometric Analysis - Nurachman, Indriyani Astuti; Heryana, Regina Putri; Luthfi, Dwi; Fitriana, F.; Santoso, Rachmat Agus (Manunggal Halim Jaya, 2025)
This study presents a bibliometric analysis of audit quality research trends using VOS viewer, examining 913 Scopus-indexed articles from 2020-2023. Through co-citation and co-occurrence analysis, we identify key developments and knowledge gaps in the field. Findings indicate sustained growth in audit quality research, with publications peaking at 288 articles in 2023 (a 29.7% increase from 2022). The intellectual structure reveals DeFond and Zhang's (2014) work as most influential (147 citations), while network analysis uncovers nine thematic clusters. Notably, we identify under-researched areas including key audit matters, AI applications, and audit efficiency metrics. The analysis particularly highlights the growing relevance of digital transformation themes - artificial intelligence, integrated reporting, and technological efficiency measures - as emerging frontiers in audit quality research. These findings provide: (1) a systematic mapping of the field's evolution, (2) quantitative validation of research trends, and (3) priority directions for future studies. The study contributes to auditing literature by offering empirical evidence of shifting research focus toward technology-integrated audit processes, suggesting the need for more work examining how digital innovations impact quality measurement and assurance practices. Practitioners and researchers can leverage these insights to align investigations with current industry demands and technological advancements in the auditing profession.